Functional importance of the Gly cluster in transmembrane helix 2 of the Bordetella pertussis CyaA-hemolysin: Implications for toxin oligomerization and pore formation. (November 2015) - Juntapremjit, Sirikran; Thamwiriyasati, Niramon; Kurehong, Chattip; Prangkio, Panchika; Shank, Lalida; Powthongchin, Busaba; Angsuthanasombat, Chanan
Abstract: Adenylate cyclase-hemolysin (CyaA) is a major virulence factor of Bordetella pertussis causing whooping cough in humans. We previously showed that two transmembrane helices (α2 and α3) in the hemolysin domain (CyaA-Hly) are crucially involved in hemolytic activity. Here, PCR-based substitutions were employed to investigate a potential involvement in hemolysis of a series of four Gly residues (Gly 530, Gly 533, Gly 537 and Gly 544 ) which map onto one face of a helical wheel plot of pore-lining helix 2. All CyaA-Hly mutant toxins were over-expressed in Escherichia coli as 126-kDa soluble proteins at levels comparable to the wild-type toxin. A drastic reduction in hemolytic activity against sheep erythrocytes was observed for three CyaA-Hly mutants, i.e. G530A, G533A and G537A, but not G544A, suggesting a functional importance of the Gly 530 _Gly 533 _Gly 537 cluster. A homology-based structure of the α2-loop-α3 hairpin revealed that this crucial Gly cluster arranged as a GXXGXXXG motif is conceivably involved in helix–helix association. Furthermore, a plausible pore model comprising three α2-loop-α3 hairpins implicated that Gly 530 XXGly 533 XXXGly 537 could function as an important framework for toxin oligomerization. Altogether, our present data signify for the first time that the Gly 530 _Gly 533 _Gly 537 cluster in transmembrane helix 2 serves as a crucial constituent of the CyaA-Hly trimeric pore structure. Highlights: α2-loop-α3 transmembrane hairpin of CyaA-hemolysin could potentially be a pore-forming constituent. Ala-substitutions at Gly 530 _Gly 533 _Gly 537 cluster in α2 of CyaA-Hly revealed its important role in hemolysis. This critical Gly cluster arranged as a GXXGXXXG motif could be implicated in helix–helix association. 3D-modeled pore comprising three α2-loop-α3 hairpins reveals potential involvement of the Gly cluster. Our trimeric CyaA-Hly pore model is in agreement with the results of Gly-to-Ala mutations.